2019
DOI: 10.2298/apt1950059d
|View full text |Cite
|
Sign up to set email alerts
|

The content of basic cannabinoids and their mutual ratios in Cannabis sativa L. plant

Abstract: Cannabinoids are typical chemical ingredients of a Cannabis sativa L. plant. The main psychoactive ingredient of this plant is Δ 9-tetrahydrocannabinol, whose content mostly determines the strength or potential of a cannabis product. In addition to this ingredient, the forensic analysis also includes determination of the presence and content of cannabidiol and cannabinol. Over the last couple of decades, there have been changes in chemical composition of cannabis products in many countries, and they manifest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…During the past few decades, reports on the concentration of THC and CBD in MSPS have shown the tendency of THC to increase on account of the CBD decrease (thus an elevated THC/CBD ratio) in Europe, the USA, Australia, and, regarding the Balkan region, in the Republic of Srpska [35][36][37][38][39]. To obtain marijuana strains with high psychoactive properties (i.e., a high THC concentration), several premises of its cultivation and growing should be considered: the genus and type of cannabis (for instance, THC is higher in sinsemilla-female marijuana plants) or selective breeding of specific cannabis strains with a high THC/low CBD level; furthermore, the controlled conditions of cannabis cultivation and growing (temperature, light, humidity, and type of soil) in the indoor and outdoor environment influence the level of THC in the cannabis plant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the past few decades, reports on the concentration of THC and CBD in MSPS have shown the tendency of THC to increase on account of the CBD decrease (thus an elevated THC/CBD ratio) in Europe, the USA, Australia, and, regarding the Balkan region, in the Republic of Srpska [35][36][37][38][39]. To obtain marijuana strains with high psychoactive properties (i.e., a high THC concentration), several premises of its cultivation and growing should be considered: the genus and type of cannabis (for instance, THC is higher in sinsemilla-female marijuana plants) or selective breeding of specific cannabis strains with a high THC/low CBD level; furthermore, the controlled conditions of cannabis cultivation and growing (temperature, light, humidity, and type of soil) in the indoor and outdoor environment influence the level of THC in the cannabis plant.…”
Section: Discussionmentioning
confidence: 99%
“…Dragoljic et al concluded that with time, the proportion of high-potency samples (THC > 10%) increases while the proportion of low-potency samples (THC 2%) decreases, leading to an overall increase in the average annual potential of the samples of seized cannabis plant material [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation